2013
DOI: 10.53102/2013.32.01.690
|View full text |Cite
|
Sign up to set email alerts
|

Impact des pratiques de management de la qualité sur l’innovation

Abstract: Il est généralement reconnu que les entreprises doivent être innovatrices afin de survivre. Certains spécialistes du management de la qualité suggèrent que la mise en place d'une approche qualité fournit une plate-forme nécessaire pour encourager l'innovation. Le principal objectif de cette étude est de comprendre la relation qui existe entre les pratiques du management de la qualité (PMQ) et l'innovation dans le contexte des entreprises tunisiennes. Pour ce faire, une étude empirique a été menée auprès d'un é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A review of the literature supports the positive correlation between TQM and organizational innovation. Several studies have found statistically significant impact of TQM on innovation (product and process innovations) (Gambi et al , 2020; Abu Salim et al , 2019; Sahoo, 2019; Escrig-Tena et al , 2018; Khan and Naeem, 2018; Honarpour et al , 2017; Antunes et al , 2017; Maistry et al , 2017: Yusr et al , 2017; Khalfallah and Lakhal, 2013; Zehir et al , 2012; Hung et al , 2011; Sun et al , 2009; Hoang et al , 2006; Perdomo-Ortiz et al , 2006; Prajogo and Sohal, 2003, 2004).…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…A review of the literature supports the positive correlation between TQM and organizational innovation. Several studies have found statistically significant impact of TQM on innovation (product and process innovations) (Gambi et al , 2020; Abu Salim et al , 2019; Sahoo, 2019; Escrig-Tena et al , 2018; Khan and Naeem, 2018; Honarpour et al , 2017; Antunes et al , 2017; Maistry et al , 2017: Yusr et al , 2017; Khalfallah and Lakhal, 2013; Zehir et al , 2012; Hung et al , 2011; Sun et al , 2009; Hoang et al , 2006; Perdomo-Ortiz et al , 2006; Prajogo and Sohal, 2003, 2004).…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%